General Comment No. 24 on State Obligations Under the International Covenant on Economic, Social and Cultural Rights in the Context of Business Activities: The Committee on Economic, Social and Cultural Rights Has Played Its Part - Grosbon, Sophie (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional)

(untitled) (Société québécoise de droit international, 2018)
In the context of discussions on the elaboration of an international legally binding instrument on transnational corporations and other business enterprises with respect to human rights, the Committee on Economic, Social and Cultural Rights adopted in 2017 the General Comment No. 24 on State Obligations under the International Covenant on Economic, Social and Cultural Rights in the Context of Business Activities. Going against neoliberal logic, the Committee promotes a welfare state that effectively circumscribes economic freedoms and that resolutely protects vulnerable populations. Among various interpretations of instruments and extraterritorial obligations, the Committee clearly chooses a teleological interpretation, without disrupting the economy of the treaty, but by decidedly opting for the control of transnational businesses by way of the only actors it can reach, given its mandate: States. The extraterritorial obligation to protect consists mainly in adopting reasonable measures (duty of diligence, judicial cooperation, fight against fiscal optimization) to prevent violations of the Covenant by a private business that the State can influence.